On the advertisement call of Dermatonotus muelleri (Boettger, 1885) (Anura, Microhylidae) - Giaretta, Ariovaldo Antonio; de Andrade, Felipe Silva; Haga, Isabelle Aquemi; Bernardes, Cyro De Sousa (Zootaxa, 2013)
As presently recognized, Dermatonotus muelleri (Boettger, 1885) occurs throughout Argentina, Bolivia, Brazil and Paraguay (Brusquetti & Lavilla 2006); Paraguay referred as the type-locality (Frost 2013). Its advertisement call was briefly described by Nelson (1973) based on a sample from Brazil. In the present work, we redescribe its advertisement call based on a large sample from the Cerrado biome of Triângulo Mineiro region, state of Minas Gerais.